Dual‐Targeted Protein MRI Contrast Agent for Early Detection of Micrometastases - Ruofan Hu; Zhiyang Wang; Tinghui Shen; Qianwen Yang; Weizhi Chen; Xiqun Jiang (Aggregate)
ABSTRACT Tumor metastasis accounts for the major portion of cancer‐related deaths. Magnetic resonance imaging (MRI) is a valuable imaging modality for tumor diagnosis in clinical applications, offering detailed soft tissue images with excellent spatial resolution and good biosafety. However, the low sensitivity and the lack of specificity to disease sites limit the application of MRI contrast agents in early and precise detection of small primary and metastatic cancers. Therefore, there is an urgent need for innovative MRI contrast agents with enhanced relaxivity, target ability, and pharmacokinetics to improve imaging sensitivity and widen the detection window in the meantime. Here, we reported a dual‐targeting protein MRI contrast agent (EPR‐DTPA‐Gd) fused by a nanobody against epidermal growth factor receptor 1 (EGFR), integrin αvβ3‐binding cyclic nonapeptide, and elastin‐like polypeptide. We found that this protein contrast agent exhibited high sensitivity and specificity for the tumor overexpressed EGFR and integrin αvβ3 in MRI. Furthermore, EPR‐DTPA‐Gd had high longitudinal relaxation rate (r1) (68.76 mM−1 s−1 per molecule) and an improved pharmacokinetics behavior for tumor imaging. Using T1‐weighted imaging, EPR‐DTPA‐Gd successfully detected a series of early metastases with the smallest 0.012 mm2 (213 µm × 58 µm) in a liver metastasis model of human cervical carcinoma HeLa cells, which cannot be detected by the clinically approved T1‐weighted contrast agent. The heightened detection sensitivity intrinsic to EPR‐DTPA‐Gd facilitates precise imaging of tumor lesions, supporting sophisticated image‐guided interventions and early management in high‐risk patient cohorts.